Species-Specific Flight Styles of Flies are Reflected in the Response Dynamics of a Homolog Motion-Sensitive Neuron - Geurten, Bart; Kern, Roland; Egelhaaf, Martin (Frontiers in Integrative Neuroscience, 2012)
Hoverflies and blowflies have distinctly different flight styles. Yet, both species have been shown to structure their flight behaviour in a way that facilitates extraction of 3D information from the image flow on the retina (optic flow). Neuronal candidates to analyse the optic flow are the tangential cells in the third optical ganglion – the lobula complex. These neurons are directionally selective and integrate the optic flow over large parts of the visual field. Homologue tangential cells in hoverflies and blowflies have a similar morphology. Because blowflies and hoverflies have similar neuronal layout but distinctly different flight behaviours, they are an ideal substrate to pinpoint potential neuronal adaptations to the different flight styles. In this article we describe the relationship between locomotion behaviour and motion vision on three different levels: 1. We compare the different flight styles based on the categorisation of flight behaviour into prototypical movements. 2. We measure the species specific dynamics of the optic flow under naturalistic flight conditions. We found the translational optic flow of both species to be very different. 3. We describe possible adaptations of a homologue motion sensitive neuron. We stimulate this cell in blowflies (Calliphora) and hoverflies (Eristalis) with naturalistic optic flow generated by both species during free flight. The characterized hoverfly tangential cell responds faster to transient changes in the optic flow than its blowfly homologue. It is discussed whether and how the different dynamical response properties aid optic flow analysis.